Determination of the density of defect states by thermally stimulated conductivity studied from numerical simulations - Schmidt, Javier Alejandro (2004)
Starting from the multiple trapping rate equations that define the non-equilibrium concentrations of electrons and holes in extended states, the thermally stimulated conductivity (TSC) experiment is examined. A system of non-linear coupled differential equations is solved to get the temporal evolution of the occupation functions and the carrier concentrations during the initial isothermal waiting time and the subsequent heating at a constant rate. The simulated TSC spectra reproduce the reported dependence of the measured spectra on the heating rate and the starting temperature. An approximate expression to obtain the DOS distribution in the upper half of the band gap from TSC spectra is deduced. The application of this expression to simulated TSC curves provides an accurate reconstruction of the introduced DOS. The TSC method compares favourably to the modulated photoconductivity experiments, both from the quality of the DOS reconstruction and the experimental simplicity of the method.